Absences from work among healthcare workers: are they related to influenza shot adherence? - Francesca Antinolfi; Claudio Battistella; Laura Brunelli; Francesca Malacarne; Francesco Giuseppe Bucci; Daniele Celotto; Roberto Cocconi; Silvio Brusaferro (BMC, 2020)
Abstract Background The coverage for influenza vaccination among healthcare workers (HCWs) is inadequate in many countries despite strong recommendations; is there evidence that influenza vaccination is effective in preventing absenteeism? Aim of the study is to evaluate the influenza vaccination coverage and its effects on absences from work among HCWs of an Italian academic healthcare trust during the 2017-2018 influenza season. Methods We performed a retrospective study to identify predictive characteristics for vaccination, and a retrospective cohort study to establish the effect of vaccination on absences among the vaccinated and non-vaccinated cohorts between December 2017 and May 2018. Overall absence rates over the whole observation period and sub-rates over 14-days intervals were calculated; then comparison between the two groups were conducted applying Chi-square test. Results Influenza vaccination coverage among 4419 HCWs was 14.5%. Age, university degree, medical care area and physician profile were positively associated with vaccine uptake. Globally during influenza season non-vaccinated HCWs lost 2.47/100 person-days of work compared to 1.92/100 person-days of work among vaccinated HCWs (p < 0.001); significant differences in absences rates resulted when focusing on the influenza epidemic peak. Conclusions Factors predicting influenza uptake among HCWs were male sex, working within medical care area and being a physician. Absenteeism among HCWs resulted to be negatively correlated with vaccination against influenza. These findings add evidence to the urgent need to implement better influenza vaccination strategies towards HCWs to tackle vaccine hesitancy among professionals.